Analytic Estimation of Two-Dimensional Electron Gas Density and Current-Voltage Characteristic in AlGaN/GaN HEMT’s - Asmae Babaya; Bri Seddik; Saadi Adil (Institute of Advanced Engineering and Science, 2018)
This paper is mainly dedicated to understand the phenomena governing the formation of two-dimensional electron gas (2DEG) confined in the quantum well which hold the role of the channel in the high electron density transistors (HEMT) based on AlGaN / GaN heterojunction. The theory takes into account: the crystal structure, the spontaneous and piezoelectric polarization concept, the formation mechanism of two-dimensional electron gas at the AlGaN / GaN interface, the approximate resolution of the Poisson and Schrödinger equations to determine the density of Two-dimensional electron gas after the analytical formula of the current-voltage characteristic is established. Our study is also concerned with the dependence of the two-dimensional electron gas density on the following technological parameters: Aluminum molare fraction, AlGaN layer thickness and AlGaN layer doping, In order to control the influence of these parameters on the device performance. Finally, the current-voltage characteristic which reflects the variation of the drain-source current as a function of the modulation of the gate voltage has been discussed.